EXPERIMENTAL GONOCOCCUS INFECTION OF THE CHICK EMBRYO - Bang, Frederik (The Rockefeller University Press, 1941)
1. The reaction of the chick embryo to nine strains of gonococci was studied. Four of these were inoculated intra-amniotically in 14 to 15 day embryos. 2. Infection of the 10 day chorio-allantoic membrane was localized and accompanied by polymorphonuclear leucocytic phagocytosis. 3. Infection was either transitory or persisted until hatching. Several strains killed the 10 day embryo in 3 days. 4. Chicken immune sera placed on the infected membranes failed to affect phagocytosis. 5. Slight sinusitis, bronchitis, and infection of the pulmonary alveoli were common following intra-amniotic injection of 14 to 15 day embryos. Infection also extended to the pulmonary and abdominal air sacs. 6. Serial passage on the membrane so modified one strain that it killed a greater percentage of both 10 day and 14 day embryos. The infection after modification was also accompanied by bacteremia and meningitis in one embryo. 7. The ability of meningococci to invade tissue and produce septicemia is contrasted with the inability of gonococci to produce more than a superficial infection. 8. The infection of the embryo with gonococci reproduces all of the essential characteristics of the disease in man. 9. Gonococci were found within columnar epithelial cells in a case of acute human urethritis.